How do elite endurance athletes self-regulate their recovery around hard training? An experience sampling study - Wilson, S. G.; Young, B. W.; Hoar, S. (Sport, Exercise, and Performance Psychology, 2025)
Effective training for high-performance sport requires recovery, yet little research has examined the psychology of how athletes shape their recovery between training sessions. Although qualitative research has described how elite endurance athletes implement recovery through self-regulatory processes, there is a need to explore how this evidence transfers to more ecologically valid contexts. This study employed experience sampling methods to describe how elite endurance athletes self-regulated their recovery around two important workouts, 2-3 days apart in their planned training. Twenty-two endurance athletes (seven males, 15 females) training within Canadian national cycling and triathlon teams (able-bodied and parasport) reported on processes of recovery self-regulation and perceived recovery and stress states using their smartphones, up to eight times daily for 5 days. We described indices and patterns for how the athletes employed four recovery self-regulation processes (i.e., awareness, checking-in, interpreting, adjusting), as well as when in relation to their key workouts and recovery-stress states. The specific self-regulatory processes were strongly correlated but differed in frequency, intensity, consistency, and predictors of use, which suggests that the processes represent synergistic yet unique competencies. Greater use of recovery self-regulation processes was associated with states of higher perceived stress and, to a lesser extent, lower perceived recovery. Although the time remaining to a workout and elapsed after a workout were each associated with perceived stress and recovery states, these timelines were not associated with any self-regulation process. Our findings indicate that elite athletes may be frequently engaged in dynamically self-regulating their recovery between important training sessions.